Oral cavity and oropharyngeal cancer incidence trends and disparities in the United States: 2000–2010. Issue 4 (August 2015) - Weatherspoon, Darien J.; Chattopadhyay, Amit; Boroumand, Shahdokht; Garcia, Isabel
Highlights: The age-standardized cumulative incidence rate for oral cancers from 2000 to 2010 was 8.4 cases per 100, 000. The tonsil was the most frequently diagnosed oral cancer site and the site with the greatest incidence from 2000 to 2010. Cancers of the oral cavity showed a decreasing trend for incidence from 2000 to 2010. Cancers of the oropharyngeal region showed an increasing trend for incidence from 2000 to 2010. Racial/ethnic and gender disparities exist for oral cancers. Abstract: Background: Changes in the incidence of oral cancer based on anatomic location and demographic factors over time have been reported in the United States. The purpose of this study was to use recent data to examine oral cancer incidence trends and disparities by demographic factors and anatomic location. Methods: Surveillance, Epidemiology, and End Results (SEER) incidence data from 2000 to 2010 were used to characterize and analyze oral cancer incidence trends by anatomic region and subsite, age at diagnosis, gender, race/ethnicity, and stage at diagnosis. Poisson regression was used to compare incidence risk by select demographic factors. Results: About 75, 468 incident oral cancer cases were diagnosed from 2000 to 2010. The tonsil was the most frequently diagnosed anatomic subsite (23.1%) and the subsite with the greatest contribution to the overall, age-standardized cumulative incidence rate of 8.4 cases per 100, 000 (95% confidence interval (CI): 8.3, 8.4). An increasing incidence trend was observed for cancers in the oropharyngeal region, in contrast to a decreasing trend seen in the oral cavity region. In the Poisson regression model, all race/ethnicity groups showed a lower incidence risk relative to whites for oral cavity and oropharyngeal cancer, and white males displayed the highest incidence rate of all race/ethnicity-gender groups during the study period (14.1 per 100, 000; 95% CI: 14.0, 14.2). Conclusions: This study's epidemiological findings are especially important for oral health care providers, patient education, and the identification of risk profiles associated with oral cancer. The distinct epidemiological trends of oral cavity and oropharyngeal cancers dictate that oral cancer can no longer be viewed as a discrete entity. Oral health providers should have a strong understanding of the different risk factors associated with oral cavity and oropharyngeal cancers and educate their patients accordingly.